A comparative study of ordinary and fastidious customers' priorities in service quality dimensions. (23rd February 2017) - Dabestani, Reza; Shahin, Arash; Shirouyehzad, Hadi; Saljoughian, Mohammad
Abstract : The current study aims to prioritise service quality dimensions (SQDs) for hotels through a two-step procedure: firstly, by forming congruent groups of customers based on their level of expectations as well as perceptions of service; and secondly, by prioritising SQDs for each group and analysing the results. To reach that aim, the customers of three four-star hotels were targeted and asked to report on the quality of the service they expected to receive prior to its delivery as well as their feelings towards the service after they received it. Then, using data envelopment analysis we discriminated the majority of customers, those who were satisfied more easily (ordinary customers), from the ones who were harder to please (fastidious customers). Finally, we exploited Technique for Order Preference by Similarity to an Ideal Solution and Shannon Entropy to prioritise SQDs for each group. The approach taken in this paper, which first distinguishes two groups of fastidious from ordinary customers based on their expectations and perceptions, is rather noble. Findings revealed that the two groups do not value different dimensions of service quality in a similar way. The results of this study can provide insightful guidance for the hoteliers to customise their service and exploit their resources more efficiently.